Meaning making in retirement transition: a qualitative inquiry into Slovak retirees. Issue 1 (1st January 2021) - Halama, Peter; Záhorcová, Lucia; Škrobáková, Žaneta
ABSTRACT: Purpose: This study is a qualitative inquiry into meaning making during retirement transition. The study focuses on how Slovak retirees reconstruct meanings during the transition and the factors which both help and hinder this process. Methods: Forty individuals (M = 63.36; SD = 2.47) who had recently transitioned into retirement were interviewed and data were analysed using the Consensual Qualitative Research-Modified approach. Results: The analysis generated five basic domains with categories and subcategories of the participants' responses. The analysis showed that once retired, the participants generally continued to rely on previous meaning sources such as work and family; however, there were changes such as switching from job-related work to work related to hobbies and housekeeping, or from financially providing for the family to maintaining family relationships and grandparenting. The main factors facilitating the meaning making process were positive attitudes and social support for meaning. The risk factors included lack of finances, poor health of retiree or a close person, and the loss of a spouse. Conclusions: In general, the research showed that the main features of the retirees' meaning making processes were maintaining accessible sources, compensating for sources lost during the transition, and managing beneficial and risk factors.